Пластичность и стабильность сортов картофеля в условиях Камчатского края : Plasticity and Stability of Potato Varieties under Conditions of Kamchatka Krai - Власенко Г.П. (Достижения науки и техники АПК, 2018)
В статье представлен сравнительный анализ показателей экологической пластичности и стабильности перспективных сортов картофеля в условиях Камчатского края. Исследования проводили в 2013-2016 гг. согласно общепринятым методикам. Изучаемые показатели оценивали по методике Эберхарта и Рассела в изложении В.А. Зыкина. Исследовали сорта Радонежский, Рябинушка, Ладожский, Ручеек, Аврора (Всеволожской селекционной станции); Югана (ВНИИКХ, СибНИИСХиТ); Сафо (СибНИИРС);Лазарь (СибНИИСХ); Гейзер(Камчатского НИИСХ); Маделине, Фреско, Сантэ (Нидерланды, два последних районированные сорта, стандарт). За годы испытания наиболее урожайными были сорта Югана, Маделине, Рябинушка, Радонежский, Сафо, Гейзер, Ладожский. На основе проведенного анализа к сортам интенсивного типа отнесены Радонежский, Маделине, Сафо (b: 1,29-1,51), к пластичным Гейзер, Югана, Рябинушка, Ладожский, Ручеек, Аврора (b: 0,73-1,02). Стабильными по годам были сорта Ручеек и Аврора, но урожайность у них на 2,0 и 2,1 т/га ниже средней по опыту. Из изученной группы сортов, с учетом комплекса хозяйственно ценных признаков, в условиях Камчатского края в сельхозпредприятиях с высоким уровнем агротехники целесообразно выращивать отечественные интенсивные сорта Радонежский, Сафо (b: 1,29-1,51), в личных подсобных, крестьянских и фермерских хозяйствах пластичные Гейзер, Югана (b: 0,73 -077). : The article presents a comparative analysis of indicators of ecological plasticity and stability of promising potato varieties under conditions of Kamchatka Krai. The studies were carried out in 2013-2016 according to the generally accepted methods. The plasticity and stability of the varieties studied were evaluated by the methods of Eberhart and Russell in the presentation of V. A. Zykin. In the study there were varieties: Radonezhsky, Ryabinushka, Ladozhsky, Rucheek, Avrora (Vsevolozhskaya breeding station); Yugana (All-Russian Research Institute of Potato Farming, Siberian Research Institute of Agriculture and Peat); Safo (Siberian Research Institute of Plant Growing and Breeding); Lazar (Siberian Research Agricultural Institute); Geyzer (Kamchatka Research Agricultural Institute); Madeleine, Fresco, Sante (Netherlands). The last two varieties are zoned varieties, the standards. For the years of the experiments, varieties Yugana, Madeleine, Ryabinushka, Radonezhsky, Safo, Geyzer, Ladozhsky were the most productive. Based on the analysis carried out, Radonezhsky, Madeleine, Safo can be classified as varieties of the intensive type (bi = 1.29-1.51); Geyzer, Yugana, Ryabinushka, Ladozhsky, Rucheek, Avrora as plastic varieties (bi = 0.73-1.02). Rucheek and Avrora varieties were stable over the years, but their productivity was lower by 2.0 and 2.1 t/ha, in comparison with the average productivity in the test. From the studied group of varieties, taking into account a complex of economically valuable traits, under conditions of Kamchatka Krai on the farms with a high level of agrotechnics, it is advisable to cultivate domestic intensive varieties Radonezhsky, Safo (bi = 1.29-1.51). For personal private farms plastic varieties Geyzer, Yugana, (bi = 0.73-0.77) are better.